Análisis doctrinario y comparado de las políticas exteriores de gobiernos socialistas en Estados afectados por el populismo en América Latina - Rios Pineda, Luis Fernando (2024)
The present Curricular Integration Work entitled. "Doctrinal and comparative analysis of the foreign policies of socialist governments in States affected by populism in Latin America". The political ideology of the rulers is an issue that is not given the necessary relevance, since it directly influences their actions with respect to economic and social policies and international relations. Key aspects for the correct development of a State. This research project is based on the socialist ideology, how its original conception and bases have been distorted and adapted in a harmful way in Latin America, because in our region these ideas have been taken by different political leaders, adapting it to the idiosyncrasy of each country and being adopted by others, thus creating a hodgepodge of precepts, ideas, conceptions, etc.. That make none of these countries follow a concise basis of what socialism really is as an ideology. The consequences of this failed adoption have varied from country to country and it depends on other factors to determine the success or failure of certain political parties, but, in general, the countries that have most defended this new way of conceiving socialism in Latin America, have called it "Socialism of the XXI Century". Whose main general characteristic, evidenced by history, has been to enter into power using our democratic tools to then manipulate them in favor of their model, modify the Constitution, destroy institutions and seek to draw a line to divide the population between rich and poor, encouraging hatred between classes; acts that have brought to these countries a series of political, economic and social problems. That is why it is so important to protect the institutions and take care of democracy, because if we lose it, there will be no international organization that can help us to recover them. The constitutional principles of citizen participation and control of government action establish mechanisms so that citizens can freely and democratically elect their representatives, access public information, express their opinions and proposals, participate in decision-making and control the management of public resources. In this context, citizen participation and control of government action become fundamental tools for the defense of democratic institutions. We citizens must be aware of our rights and responsibilities. We must actively participate in public life to demand transparency, accountability and responsible government.